Development of Path Loss Models for Smooth and Convex Surfaces Terrains in Malaysian Environment - Wong, Peng Kiong (2004)
This study describes the development of path loss prediction model for smooth and convex surfaces terrains in Malaysian environment. The measurement system consists of a spectrum analyzer and a log-periodic antenna. A computer program was developed to acquire measured field strength data from the spectrum analyzer and convert the values to path loss using Agilent Visual Engineering Environment (VEE). Both line-of-sight propagation (for smooth terrain) and non-line-of-sight propagation (for convex surface terrains) was investigated in the Serdang area. The measured path losses was compared with various path loss prediction models such as free space loss (FSL), plane earth loss (PEL), Walfisch-Ikegami LOS (WI), Epstein-Peterson (E-P), Deygout (D), Edward-Durkin (E-D), Blomquist-Ladell (B-L) and Giovanelli (G). The results show that these entire models gave unsatisfactory results when compared with the measured path losses, where for smooth terrain, the FSL, PEL and WI models overestimated the path loss as high as 72%, 70% and 23%, respectively and for single and double convex surfaces terrains, the E-P, D, E-D, B-L and G models overestimated the path loss as high as 25% in all measurement frequencies. Because of and an improved version of the E-P and G models have been developed to suit these three regions and the accuracy of these entire models was tested where the mean error values were found to be approximately 5% for all the measurement frequencies. An integrated UPMPL path loss model for both smooth and convex surfaces terrains has been developed and implemented using Agilent VEE. The UPMPL program provides the utility for calculating the signal characteristics of radio propagation paths and is realized in the run time format version. This program consists of four algorithms which are conversion formulas, smooth terrain, single convex surface terrain and double convex surfaces terrain.